2022
DOI: 10.1136/bmjopen-2021-055217
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of OP/Na swabbing for SARS-CoV-2: a prospective observational cohort surveillance study in Western Australian schools

Abstract: ObjectivesWhen the COVID-19 pandemic was declared, Governments responded with lockdown and isolation measures to combat viral spread, including the closure of many schools. More than a year later, widespread screening for SARS-CoV-2 is critical to allow schools and other institutions to remain open. Here, we describe the acceptability of a minimally invasive COVID-19 screening protocol trialled by the Western Australian Government to mitigate the risks of and boost public confidence in schools remaining open. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Testing with combination specimen types (e.g., sampling from both the throat and anterior nares) was inferred to yield significantly improved clinical sensitivity to detect both infected ( Fig S6, S7 ) and presumed infectious individuals ( Fig 6-7 ) than any single specimen type, regardless of whether the combination specimen type was assumed to have the maximum or the average viral load of constituent specimen types ( Fig S7 ). Combination swabs have high acceptability(77), and are already common in many regions of the world. In the U.K., the National Health Service website even states that PCR tests that rely only on nasal swabbing will be “less accurate” than those with a combined nose and tonsil swab(78, 79).…”
Section: Discussionmentioning
confidence: 99%
“…Testing with combination specimen types (e.g., sampling from both the throat and anterior nares) was inferred to yield significantly improved clinical sensitivity to detect both infected ( Fig S6, S7 ) and presumed infectious individuals ( Fig 6-7 ) than any single specimen type, regardless of whether the combination specimen type was assumed to have the maximum or the average viral load of constituent specimen types ( Fig S7 ). Combination swabs have high acceptability(77), and are already common in many regions of the world. In the U.K., the National Health Service website even states that PCR tests that rely only on nasal swabbing will be “less accurate” than those with a combined nose and tonsil swab(78, 79).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to eliminating the drawbacks of nasopharyngeal swabs in terms of causing discomfort and possibly even damage to the patient [ 56 ], nasal swabs offered the option of home testing. Questionnaires were conducted in several studies, resulting that nearly all patients reported no pain in the anterior nasal collection, and it was easy to understand how to perform self-testing and interpret the test results [ 3 , 4 , 6 , 47 , 53 , 57 ]. Previous experience with HIV self-testing demonstrated that self-testers could perform HIV rapid diagnostic tests with reliability and accuracy [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although PCR swabs from the nose and throat were the gold standard during the pandemic, this type of swab was uncomfortable which may impact of the quality of these swabs in younger age groups. 34 Saliva PCR testing may prove to be more acceptable to young children and therefore be of use in monitoring incidence. 35 , 36 , 37 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%